Assessing the sustainability literacy of the Nigerian engineering community. (1st March 2019) - Akeel, Usman; Bell, Sarah; Mitchell, John E.
Abstract: Being the lifeblood of socioeconomic progress, engineering is implicated in the unprecedented challenge of sustainability. The global engineering community devised sustainable engineering as a conceptual departure from conventional engineering practices. However, the extent to which the sustainability worldview has permeated the Nigerian engineering community remains unanswered. This paper is an attempt to answer the question of how sustainability literate are the members of the Nigerian engineering community. The paper undertakes an assessment of the sustainability literacy of the community with the aid of a stakeholder survey and a devised sustainability literacy test. Three criteria that are used to gauge the stakeholders' sustainability literacy are awareness of the UN Decade of Education for Sustainable Development, score on the sustainability literacy test, and self-assessment of sustainability knowledge. Survey participants were recruited mainly from two federally-run Nigerian higher education institutions, and engineering professional associations. The assessment reveals an unsatisfactory performance of the Nigerian engineering stakeholders on all three sustainability literacy criteria. The results show that the majority of the students (81%), educators (67%), and practitioners (64%) were unaware of the UNDESD. The paper therefore highlights the need to improve the sustainability literacy of the Nigerian engineering community, possibly through a sustainability education intervention.